Seismic Fragility Analysis of the Transmission Tower-Line System Considering Bolt Slippage - Jia-Xiang Li; Chao Zhang; Jin-Peng Cheng (Applied Sciences)
Seismic fragility analysis can directly reflect the damage probability of the transmission tower-line system and effectively evaluate the seismic performance. To accurately estimate the failure probability of transmission tower-line systems under earthquakes, the tower-line system model considering bolt slippage was established in this paper. Subsequently, through the pushover analysis, different limit states of transmission lines subjected to earthquakes were determined. Finally, 15 seismic waves were selected to study the seismic fragility of a tower-line system by conducting an incremental dynamic analysis on the tower-line system, and seismic fragility curves were drawn. The influences of bolt slippage and foundation deformation on the seismic fragility of the tower are discussed. The results show that the bolt slippage behavior can affect the seismic fragility of tower-line systems and has opposite effects on the transmission tower with a fixed foundation and the transmission tower with foundation deformation.